Characterization of the Quality and Flavor in Chinese Sausage: Comparison Between Cantonese, Five-Spice, and Mala Sausages - Xuemei Cai; Yi Zeng; Kaixian Zhu; Yiqin Peng; Pei Xv; Ping Dong; Mingfeng Qiao; Wenjiao Fan (Foods)
With the increasing popularity of traditional Chinese sausages both domestically and internationally, the flavor characteristics of sausages have become an important topic in food science research. However, comparative studies on the flavor differences between different types of traditional Chinese sausages are still limited. This study aimed to systematically compare the flavor profiles of three representative types of traditional Chinese sausages (Cantonese, Five-Spice, and Mala sausages), with 20 samples randomly selected from one batch of 100 sausages per type produced in December 2024, using a combination of headspace gas chromatography–ion mobility spectrometry (HS-GC-IMS), amino acid analysis, electronic sensory analysis, and sensory evaluation techniques. Sensory evaluation revealed that Mala sausage exhibited a strong and numbing flavor. Cantonese sausage was characterized by sweet and alcoholic notes, while Five-Spice sausage displayed a more subtle and gentle flavor profile. A total of 39 volatile compounds were identified, with 2-methyl-1-butanol, 2-butanone, and butanal being the most abundant across all samples. Orthogonal partial least squares discriminant analysis (OPLS-DA) further pinpointed (+)-limonene, (Z)-ocimene, α-terpinene, β-myrcene, β-pinene, γ-terpinene, 2-pentanol, 2-octanone, and 1-hexanal as the key differential compounds responsible for the distinct flavor characteristics of each sausage type. Additionally, the free amino acid content in Mala sausage was significantly higher than that in the others, with glutamic acid and proline playing pivotal roles in shaping the taste profiles. These findings provide valuable theoretical and technical insights for the identification and control of flavor in sausage production, offering a scientific basis for guiding consumer preferences in sausages’ selection.